Journalist's Information Organizational Patterns in Reporting Indonesian Vice President's Agenda - Firmansyah Firmansyah; Ashabul Yamin Asgha (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2020)
The study illustrates the pattern of organizational communication on journalist's coverage in the Vice President's agenda. Journalists from various media form informational organizations in fulfilling the task of getting news. This study used a constructivist paradigm with a descriptive qualitative approach. The method used was a case study. Data collection was done by observing the journalist's communication patterns when reporting the vice president's agenda. In-depth interviews were conducted to journalists who conducted coverage in the vice president's office in 2019 and the vice president's secretariat. Other data were obtained from documents. This study found that organizational information communication was formed between journalists, vice president secretariat, and vice president itself. In terms of reporting, journalists follow information from the vice president's secretariat. However, journalists have many ways to get information about the Vice President's internal agenda. Communication patterns showed that journalists do their work by pursuing information from several sources.